Simultaneous enhancement of specific capacitance and potential window of graphene-based electric double-layer capacitors using ferroelectric polymers - Viet ThongLe (Journal of Power Sources, 2021)
Despite their high power density, aqueous-based electric double-layer capacitors (EDLCs) possess relatively low energy density due to the limitation of potential window (~1.0 V) and low specific capacitance of active materials. To increase the energy density without sacrificing the power density, it is highly desired to achieve a simultaneous improvement of both specific capacitance and potential window of EDLCs. However, this remains a major challenge that is not been solved up to date. This work demonstrates that by inserting a polarized-polyvinylidene fluoride (PVDF) ferroelectric layer underneath the graphene, a simultaneous enhancement of both areal capacitance and potential window is achieved, in which the areal capacitance increases from 5.5 to 7.5 μF/cm2 (i.e., 36%) (or 55 F/cm3 to 75 F/cm3 in terms of volumetric capacitance), and the potential window expands from 1.0 V to 1.5 V. This results in a threefold increase in the areal energy density of the capacitor. The enhancement in capacitance can be explained by the Gouy–Chapman–Stern model. The widening of potential window is due to the shift of the Fermi level of graphene caused by the doping effect of the polarized-PVDF layer.